A cultura regionalista em Cinzas do Norte e sua tradução (cultural) para a língua inglesa - Remundini, Elerson Cestaro (2013)
This research reconstructs and evaluates the cultural framework - which is regionalist and capabie of particularizing an area and a population - in Cinzas do Norte and investigates the transiation of this novel into English (Ashes of the Amazon), by John Gledson. In both cases this research tries to estabiish a theoretical dialogue based on a (sometimes) polemical argumentation that focus on transiation and culture concepts, as weil as their taxonomical and operationai ramifications. We start by the assumption that human kind has aiways faced needs that must be supplied. Some of them are universal as they can be detected - at different levels, though - in any societies. Nevertheless, each society meets their needs in distinctive manners. The different ways of meeting those necessities are what we call cultural phenomenon. That is the reason why culture can be considered the way a group is organized and, consequently, its identity, which rnakes the group particular in relation to others. This notion is vital for this research, which firstly intends to reveal the particularity of a certain social group: the population of Manaus and the area around, presented in the novel Cinzas do Norte, by Milton Hatoum. People from a certain historicai period try to supply their needs according to the conditions ofthe place where they live, thus, building themselves culturally. That is the premise that allows the particularization (at which we aim) of the Amazonian culture (including Manaus). This particularization is here based on the novel mentioned above and takes into consideration elements of material culture, as well as "immaterial", which includes habits, traditions, behaviors, ideologies. We aim, in the first chapter, at establishing the cultural thematic panei in Cinzas do Norte. That justifies the fact that the novel is here deemed to be regionalist fiction, and that invoives supposing a specific space and a cultural set related to that space. Such set is here defined by the identification, classification and evaluation of symbolic modeis converted into language fuli of cultural and ideological information. We believe that language conveys ideology and, as a result, culture. The theoretical framework of this first stage (which is basically social and socio-anthropological) is based, above all, on the contributions of Clifford Geertz (1989) and Luiz Gonzaga de Mello (2000), among others. Once the cultural panei of Cinzas do Norte has been defined, we will deai with Ashes of the Amazon, which complements the corpus of this research. Regarding cultural transiation, we intend to investigate, with theoretical support, the translationai solutions used by John Gledson, so that we will be abie to verify how he managed to translate the cultural framework of the novel. In other words, we intend to investigate the eventual transformations of the symbolic models during the conversion. That is why the analysis proposed goes beyond the iinguistic aspects of translation, even though such aspects are also relevant when it comes to cultural translation. The evaluation of the translation solutions is processed taking into account notions from both the structuralist and postmodern perspectives of translation studies. The resuits of this research point to the fact that Ashes of the Amazon is a new text. However, it did not stop the symbolic models of the original from appearing in the translation, despite the cultural and linguistic differences that are inherent in any translation. Considering the cultural particularization, it is possible to conclude that the translation managed to relocate the cultural framework satisfactoriiy, enabling the reader to comprehend it in a satisfactory way too.